Chirality of coiled coils: elasticity matters. - Neukirch, S; Goriely, A; Hausrath, A (2008)
Coiled coils are important protein-protein interaction motifs with high specificity that are used to assemble macromolecular complexes. Their simple geometric organization, consisting of alpha helices wrapped around each other, confers remarkable mechanical properties. A geometrical and mechanical continuous model taking into account sequence effects and based on the superhelical winding of the constituent helices is introduced, and a continuous family of solutions in which the oligomerization interactions are satisfied is derived. From these solutions, geometric and structural properties, such as the chirality and pitch of the coiled coil and the location of residues, are obtained. The theoretical predictions are compared to x-ray data from the leucine zipper motif.